2019
DOI: 10.1007/s42399-019-00060-x
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Management of Chronic Non-cancer Pain and Treatment-Related Adverse Events in Asia: Perspectives from Patients from 10 Countries/Regions

Abstract: Findings from the published ACHEON study revealed inadequate pain relief for chronic non-cancer pain (CNCP) across 10 Asian countries/regions. Hence, we performed additional analyses on the survey data to understand management practices for relieving CNCP and treatment-related adverse events (AEs). Descriptive statistics were used to summarize patients' profile, prescribed treatments, and associated AEs. Two-sample t test was used to compare pain levels between treatment groups. Univariate analyses were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
(54 reference statements)
0
9
1
Order By: Relevance
“…Unfortunately, their expectations regarding medication efficacy are often unrealistically high (e.g., expecting complete pain relief), and these expectations are seldom discussed with healthcare professionals to jointly establish realistic and achievable therapeutic goals (23). Moreover, a substantial proportion perceive their treatment as inadequate (37%-64%) (24,25). The heterogeneity of people living with CP who present with different comorbidities and symptoms of pain may complexify the multimodal approaches proposed by healthcare professionals (26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, their expectations regarding medication efficacy are often unrealistically high (e.g., expecting complete pain relief), and these expectations are seldom discussed with healthcare professionals to jointly establish realistic and achievable therapeutic goals (23). Moreover, a substantial proportion perceive their treatment as inadequate (37%-64%) (24,25). The heterogeneity of people living with CP who present with different comorbidities and symptoms of pain may complexify the multimodal approaches proposed by healthcare professionals (26).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the efficacy of the multimodal approach in realworld clinical settings and unveiling modifiable factors associated with greater pain relief could help provide manageable solutions to alleviate CP and to improve its management, especially for persons without access to facilities offering multidisciplinary care. However, the evidence regarding the efficacy of pain treatments comes mainly from the results of experimental or quasiexperimental clinical trials (14,15,24,25,27). To our knowledge, a few observational studies representing the realworld have examined self-reported pain relief experienced by people living with CP in the community with their diverse array of treatments (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain is a common problem among adults, with prevalence studies suggesting that one in five are affected [ 1 , 2 ]. Despite considerable advances in our understanding, diagnosis, and management of pain, many patients report inadequate pain control [ 2 , 3 , 4 , 5 ]. Effective pain management strategies are needed to address unrelieved pain among this population.…”
Section: Introductionmentioning
confidence: 99%
“…The aims of treatment in these patients focus on reducing pain scores and improving function and quality of life. However, many patients continue to suffer from pain after receiving long-term non-opioid and non-pharmacological therapy [ 5 ]. Opioids are potent pain medications for moderate to severe pain management.…”
Section: Introductionmentioning
confidence: 99%